Expansion of the Double Pendulum System and Its Decomposition Model: Systematic Literature Review - Anisa Zulfa Nadia; Joko Siswanto; Joko Saefan (Universitas Negeri Semarang, 2025)
Double pendulum is a mechanical system that exhibits complex dynamic behavior, often used to study nonlinear dynamics and chaos. Along with the development of research, this system has been extended with the addition of several new constraints. This research aims to conduct a Systematic Literature Review (SLR) related to the extension of the double pendulum system and the formulation of the relevant equations of motion. The article search was conducted systematically, resulting in 27 documents that met the inclusion criteria. The results of the analysis show that the extension of the gantry pendulum crane system with a payload is the main focus in this study. In addition, the most frequently used decomposition model is a mathematical model with a Lagrangian approach. These findings provide deep insights for further development of mathematical models as well as their applications in the fields of robotics, system control, and dynamic structural analysis.